Sistem Pakar Diagnosis Penyakit Telinga Hidung Tenggorokan (THT) Menggunakan Metode Naive Bayes Berbasis Android - Faris Abdi El Hakim; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Ears, nose, throat are important organs contained in the human body as they relate to the hearing and respiratory system. Knowledge of ENT disease is need to solve problem of ENT disease quickly and precisely, sometimes people assume trivial ENT problems such as dry throat can be very dangerous for the health of the body and the ratio of population in Indonesia with a limited doctor to make people have to queue for a long time to the institution hospital local. That problems can be solved using expert system. Many methods that can be used, one of them is by using the method of Naive Bayes Classifier. Advances in technology such as google's android operating system that controls the technology world, based on a compass (2012) that sold 1.1 billion over the next 12 months this estimate rose from 26% from 2013 that already sold 900 million units. Causing an expert system based android to be created by the author will make the user easy to access and use it. In this system receives input data symptom of ear, nose, throat (ENT) and processed using Naive Bayes algorithm that the output of the system in the form of diagnosis of disease type and treatment of disease outcome.Based on the results of accuracy testing of 25 data has an accuracy of 92%.